From Mouth to Brain: Neuroendocrine Markers Play as a Crosstalk Among Oral and Neurodegenerative Diseases - Tatullo, Marco; Codispoti, Bruna; Makeeva, Irina; Benincasa, Caterina; Spagnuolo, Gianrico (Frontiers in Endocrinology, 2019)
The neuroendocrine system consists of various cells distributed in non-endocrine functional structures, able to synthesize amines and peptides with both local (paracrine) and systemic (endocrine) effects. The identification of such cells, belonging to the neuroendocrine system, is carried out by highlighting specific neuroendocrine markers, such as chromogranin A, synaptophysin, S-100B protein and glial fibrillary acidic protein. The presence of neuroendocrine markers is commonly associated to the occurrence of neuroendocrine cancers, currently representing the 0,5 percent of all malignant tumours. Nevertheless, neuroendocrine markers have been found to be overexpressed in rare oral neuroendocrine tumors, but also in quite common inflammatory conditions, such as severe periodontitis. The monitoring of neuroendocrine markers is, thus, a common factor of interest among dentistry and neurology: the analysis of neuroendocrine markers in oral diseases may be predictive and prognostic about the severity of neurological diseases, such as lateral amyotrophic sclerosis and traumatic brain injuries.